2002
DOI: 10.1124/dmd.30.10.1063
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activation of 4-Hydroxyanisole by Isolated Rat Hepatocytes

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:A tyrosinase-directed therapeutic approach for treating malignant melanoma uses depigmenting phenolic prodrugs such as 4-hydroxyanisole (4-HA) for oxidation by melanoma tyrosinase to form cytotoxic o-quinones. However, in a recent clinical trial, both renal and hepatic toxicity were reported as side effects of 4-HA therapy. In the following, 4-HA (200 mg/kg i.p.) administered to mice caused a 7-fold increase in plasma transaminase toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 30 publications
2
46
0
Order By: Relevance
“…The RNAi insert sequences found in these plasmids were GTAGCCGATTGGAGGAGTACA, and CCAGAAGCTGACAGGAGATGA, and GACGACTCTTG GTGAGAAGAA, and TGAGCTTGCTGTGTCGTCACA and the non-specific scrambled sequence ggaatctcattcgatgc atac was used as a control. The tyrosinase-proficient SK-MEL-28 cells (2x10 6 ) were transfected with the 1 μg plasmid DNAs (of all shRNA clones) for 48 h using the FuGENE6 reagent (Roche Diagnostics Corporation, Indianapolis, IN). The cells were trypsinized, pelleted and washed twice with cold PBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RNAi insert sequences found in these plasmids were GTAGCCGATTGGAGGAGTACA, and CCAGAAGCTGACAGGAGATGA, and GACGACTCTTG GTGAGAAGAA, and TGAGCTTGCTGTGTCGTCACA and the non-specific scrambled sequence ggaatctcattcgatgc atac was used as a control. The tyrosinase-proficient SK-MEL-28 cells (2x10 6 ) were transfected with the 1 μg plasmid DNAs (of all shRNA clones) for 48 h using the FuGENE6 reagent (Roche Diagnostics Corporation, Indianapolis, IN). The cells were trypsinized, pelleted and washed twice with cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Using this approach, 4-hydroxyanisole (4-HA) was investigated in melanoma clinical trials but was withdrawn due to liver and kidney toxicity (8). We have previously reported that 4-HA was also bioactivated by liver P450 enzymes to reactive oquinone, which contributed to its liver toxicity (6). Because drug metabolism, pharmacokinetics and drug induced liver and kidney toxicity continue to be major limiting factors in today's drug discovery endeavors, our efforts were directed towards optimizing lead phenolic-based prodrugs with selective efficacy towards melanoma but with minimal liver and kidney toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors propose that ring epoxidation and/or P450-mediated one electron oxidation as bioactivation routes to convert 4-methoxyphenol to the reactive intermediate species, 4-hydroxyanisole epoxide and p-quinone, occurs rather than O-demethylation / ring hydroxylation / ipso attack mechanism. The cytotoxicity of 4-methoxyphenol results from covalent binding of hydroquinone / p-quinone to proteins rather than from oxidative stress (Moridani et al, 2002).…”
Section: Candidate Substancesmentioning
confidence: 99%
“…The authors propose that ring epoxidation and/or P450-mediated one electron oxidation as bioactivation routes to convert 4-methoxyphenol to the reactive intermediate species, 4-hydroxyanisole epoxide and p-quinone, occurs rather than O-demethylation / ring hydroxylation / ipso attack mechanism. The cytotoxicity of 4-methoxy-phenol results from covalent binding of hydroquinone / p-quinone to proteins rather than from oxidative stress (Moridani et al, 2002).…”
Section: -Methoxyphenol [Fl-no: 04077]mentioning
confidence: 99%